Study of the Irradiation Damage in Simple Crystals by Channeling - Kokkoris, M.; Huber, H.; Kossionides, S.; Paradellis, T.; Zarkadas, Ch.; Gazis, E. N.; Vlastou, R.; Aslanoglou, X.; Assmann, W.; Karamian, S. (HNPS Advances in Nuclear Physics, 2019)
Several experiments have been carried out in the past in order to examine the impact of medium and heavy ions in crystals in the MeV range, which is of particular interest in high energy implantations. In the present work, the gradual amorphisation of simple crystals such as Si (100), Ge (100) and W (100) when irradiated with 18 MeV 1 6 0 in a random direction is being studied using the progressive change of channeling parameters, up to a maximum dose of approximately 1Ί01 6 par tides/en*2. The results are compared to the ones present in literature and an attempt is made in order to explain the peculiarities of the experimental spectra.